Lithuanian historical conception according to Ignas Onacevičius - Algirdas Šidlauskas (Lietuvos Istorijos Studijos)
We know nothing about the manuscript of „Lithuanian History" written by l. Onacevičius, but how he understood history can be understood from his letter to Teodoras Narbutas. In these letters was formed not only his advice to the author of „Lithuanian Nation History," but, as became clear to l. Onacevičius, Lithuanian historical conception as well. According to his opinion, there must be a separate volume for mythology. He was sorry, that there was no list of names nor places. He also articulated his opinion about the rights of the Grand Dukes. According to l. Onacevičius' opinion, until the end of the 14th century Grand Dukes had absolute power, and only in the time of Jogaila did the power of noblemen come into existence. l. Onacevičius explained that the nobility's freedom existed in documents, but not in real life. In general, there was no big difference in Lithuania between estates, until the wedding of Jogaila with the Polish queen; this is when the union between Lithuania and Poland began.